2005
DOI: 10.2139/ssrn.684403
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making: Tourism and Hospitality Game

Abstract: This paper introduces the reader to an experiment that proposes an expanded format of cooperative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In the present study, some students reported having gained a deeper insight into current educational problems throughout the process of the simulation, while some others realised about their learning more towards the end, in the debriefing. These findings are in line with previous studies by Thompson and Dass (2000), Brozik and Zapalska (2002, 2003); Sottile and Broznik (2004); and Tipton et al, (2016) in that they confirm that participants in a simulation perform better in terms of understanding educational issues than those who only analyse and discuss isolated cases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, some students reported having gained a deeper insight into current educational problems throughout the process of the simulation, while some others realised about their learning more towards the end, in the debriefing. These findings are in line with previous studies by Thompson and Dass (2000), Brozik and Zapalska (2002, 2003); Sottile and Broznik (2004); and Tipton et al, (2016) in that they confirm that participants in a simulation perform better in terms of understanding educational issues than those who only analyse and discuss isolated cases.…”
Section: Discussionsupporting
confidence: 92%
“…When it comes to teacher training, early research provides evidence of participants’ performance in simulation broadly, as for example, student teachers who participate in classroom simulations perform better in terms of self-efficacy than those who only analyse and discuss isolated cases (McCrary & Mazur, 2010; McGarr, 2021; Thompson & Dass, 2000). Brozik and Zapalska (2002, 2003) and Sottile and Broznik (2004) use simulation in their teacher education because of their need to find a didactic approach that replicates real classroom situations, but they do not analyse if all participants can be suitable for simulation-based instruction. The aim of their application of simulation is to explore decision-making techniques.…”
Section: Introductionmentioning
confidence: 99%